Descriptive Study: Nutrition Knowledge, Physical Activity, and Nutritional Status of 11th-Grade Students at SMA Muhammadiyah 2 Surabaya - Amira Salsabil; Nuning Marina Pengge; Juliana Christyaningsih; Riezky Faisal Nugroho (Journal of Nutrition Explorations, 2025)
Adolescence is a critical period of rapid growth and behavioral change that influences nutritional needs and lifestyle choices. This study aims to describe the nutrition knowledge, physical activity levels, and nutritional status of 11th-grade students at SMA Muhammadiyah 2 Surabaya. A descriptive study was conducted involving 58 students selected through proportional random sampling. Data were collected using validated questionnaires on nutrition knowledge and physical activity, as well as anthropometric measurements. Nutritional status was assessed using BMI-for-age and categorized based on WHO z-score standards. Data were analyzed using SPSS with univariate and bivariate methods. The majority of respondents were female (67.2%) and aged 16 (65.5%). Most had high nutrition knowledge (70.7%), engaged in light physical activity (74.1%), and had normal nutritional status (60.3%). It is recommended that schools enhance regular nutrition education, promote physical activity, and monitor students' nutritional status to support healthy adolescent development.